ANALYSIS OF CUSTOMER SERVICE AT BIKE STORES AT RECOVERY BIKE LANGOWAN - Ronaldo Jordan Poluan; Frederik G. Worang; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2023)
The purpose of this research is to analyze customer service at bike store at recovery bike Langowan. This research used qualitative method. 15 samples were collected with interview questions to the customers of Recovery bike Langowan. The result of this research shows that the service at the store Recovery bike Langowan from the interview results can be seen from the numbers of customer handled, level of customer satisfaction, response speed at the start and customer retention rate most of the respondent perceived a good service and leads to good customer service that been conducted from the store and leads them to loyal customers and become agent of marketing of the store also the performance and the marketing can conclude has a big positive impact both for the customers and the store. Keywords: customer service